A Scalable Ka-band 1024-element Transmit Dual-Circularly-Polarized Planar Phased Array for SATCOM Application - Luo, Xuan; Ouyang, Jun; Chen, Zhihui; Yan, Yi; Han, Lei; Wu, Zubing; Yu, Tao; Zheng, Kai (IEEE access, 2020)
This paper presents a scalable 1024-element transmit dual-circularly-polarized phased array for Ka-band satellite communication (SATCOM) terminal applications. The transmit array based on the CMOS beamformer and a multilayer printed circuit board (PCB) can steer up to large scan angles (±600°) with a scan loss less than 4.5 dB. With the 8-channel transmit beamformer, the array can realize dual circular polarization and the axial ratio (AR) of the array is less than 3 dB in the scanning range of ±300° in both lefthand circular polarization (LHCP) and right-hand circular polarization (RHCP) mode. The effective isotropic radiated power (EIRP) of the array achieves 74 dBm from 29.5 GHz to 30 GHz. The design and measurement of the 1024-element transmit array have presented a feasible way for mass production of a low cost active phased array.